Creep Modeling in An Orthotropic FGM Cylinder - Singla, Ashish; Garg, Manish; Deepak, Dharmpal; Gupta, V. K. (Asian Review of Mechanical Engineering, 2012)
A mathematical model has been developed to estimate steady state creep in an orthotropic cylinder made of functionally graded composite. The FG cylinder is assumed to undergo creep according to Power law. The model developed has been used to investigate the steady state creep response of the FGM cylinder for varying orthotropicity of the material. The results obtained are compared with those estimated for a similar FGM cylinder but having isotropic properties. The result reveals that the presence of orthotropicity in the FGM cylinder may significantly modify its creep response.